(untitled) (Fiep Bulletin - online, 2012)
This article is intended to clarify that the practice of regular physical activity has a key role in preventing and controlling non-communicable chronic diseases, as well as in improving dimensions of quality of life, and one of these means is the practice of swimming, a sport that works with body movement as a whole, helping to reduce body fat percentage, alleviating the daily stress and still in recovery from injuries. It aims to verify the degree of influence of this modality in improving the quality of life for practitioners. It was used in the present study a descriptive field research with a quantitative approach. The environment for this study was the city of Maracanaú, at unity SESI – Partnership Club. Taking part in the survey 40 students enrolled in the sport with at least 3 months of practice. Data collection was made using the Brazilian Version of SF-36 questionnaire, with closed and multidimensional, and met all inclusion and exclusion criteria, as well as the ethic in research process. We conclude that regular swimming helps to improve the quality of life of individuals, relating to his period before the practice.